PENERAPAN PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA POKOK BAHASAN PERUBAHAN MATERI KELAS VII SMP - Bronika Septiani Sianturi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to improve student learning outcomes by using the make a match learning model on the subject of changes in class VII material in Sibabangun 2 Public Middle School. This type of research is a quasi-experimental study with two groups pre-test and post-test research designs. The population of this study was all class VII students, amounting to three classes. From the data analysis for the experimental class, pre-tests (46.50 ± 8.53) and post-tests (81.5 ± 7.85) were obtained. In the control class, pre-tests (32.7 ± 9.54) and post-tests were obtained (64.2 ± 11.41). Both data are normally distributed. The results of testing hypotheses using the one-party t test at = 0.05 and dk = 48 obtained tcount> ttable or 4.513> 2.154 then Ha is accepted, Improving student learning outcomes after being given treatment of the make a match learning model is better than conventional learning on the subject discussion of Material Changes.Keywords: Make a Match, Learning Outcomes, Learning